A preliminary study of peripheral T‐cell subsets in porokeratosis patients with MVK or MVD variants. Issue 1 (16th December 2021) - Tao, L.; Huang, Y. K.; Yan, K. X.; Li, C. H.; Shen, L.; Zhang, Z. H.
Abstract: Background: Porokeratosis (PK) is considered a skin‐specific autoinflammatory keratinization disease. Intriguingly, four causative genes of PK are in turn arranged in mevalonate pathway, with MVD variants being the commonest followed by MVK variants in a cohort of Chinese patients. Evidence indicates that mevalonate metabolites induce trained immunity in human monocytes and regulate T cells at multiple levels. Of note, γδT cells are dually regulated by intracellular and extracellular mevalonate metabolism. Aims: To identify the possible differences in T‐cell between MVK or MVD variants from PK patients. Materials & Methods: Targeted exome sequencing and exonic CNV screening were performed in 26 patients with PK. Sanger sequencing was used to validate all identified variants. Among them, 22 patients were identified with MVK or MVD variants. PBMCs from 22 PK patients and 27 normal controls (NCs) were analysed by flow cytometry for the frequencies of T cells subsets, including IFN‐γ‐, and TNF‐α‐producing T cells. Results: There were 14 mutations identified in the 26 PK patients, including 6 novel mutations ( MVK : c.118_226+1337dup, c.388_392delGATATinsC, c.613A>T, c.768G>C, and MVD : c.250C>T, c.988T>G). In contrast to NCs, significantly decreased frequencies of CD8 + and Vγ9Vδ2 T cells were observed in the PK patients with MVD variants. Moreover, it was found that dysregulated secretion of pro‐inflammatory cytokines by T cells in both PK patients with MVK and MVD variants. Conclusions: Our findings enriched the Human Gene Mutation Databases and showed probable differences in peripheral T cells subsets between PK patients and controls. Abstract :